Cyclic behavior of post-tensioned slab-rectangular column connections - Himawan, Aris (2014)
This paper describes testing of three interior post-tensioned slab-column connections having rectangular columns with a column aspect ratio of 5. The first specimen was tested under gravity load only. The second specimen was subjected to gravity and unidirectional cyclic lateral loading, and the third specimen was subjected to gravity and bidirectional cyclic lateral loading. It was confirmed that the strength and stiffness of the connections are much higher along the strong column direction than those along the weak column direction. The test results also indicate that bidirectional cyclic lateral loading significantly reduces the strength, drift capacity, ductility, and stiffness of the connections. The increase in shear strength due to prestressing for connections having rectangular columns tends to be lower compared with those having circularsquare columns. Furthermore, a modification to the ACI shear strength equation is proposed to make the prediction conservative for connections having rectangular columns.